Preclinical models of myocardial infarction: from mechanism to translation. (11th August 2021) - Martin, Tamara P.; MacDonald, Eilidh A.; Elbassioni, Ali Ali Mohamed; O'Toole, Dylan; Zaeri, Ali Abdullah I.; Nicklin, Stuart A.; Gray, Gillian A.; Loughrey, Christopher M.
Abstract : Approximately 7 million people are affected by acute myocardial infarction (MI) each year, and despite significant therapeutic and diagnostic advancements, MI remains a leading cause of mortality worldwide. Preclinical animal models have significantly advanced our understanding of MI and have enabled the development of therapeutic strategies to combat this debilitating disease. Notably, some drugs currently used to treat MI and heart failure (HF) in patients had initially been studied in preclinical animal models. Despite this, preclinical models are limited in their ability to fully reproduce the complexity of MI in humans. The preclinical model must be carefully selected to maximise the translational potential of experimental findings. This review describes current experimental models of MI and considers how they have been used to understand drug mechanisms of action and support translational medicine development. LINKED ARTICLES: This article is part of a themed issue on Preclinical Models for Cardiovascular disease research (BJP 75th Anniversary). To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.5/issuetoc